Synthesis and Evaluation of Aromatic Surfactants as Potential Antibacterial and Cytotoxic Agents - Barrantes Jiménez, Kenia (2019)
Two ether and one ester derivatives of the 4-nitro-3-hydroxybenzoic acid were synthesized and characterized. The in vitro antimicrobial and cytotoxic activities of the three novel compounds were also evaluated. The aromatic derivatives showed antibacterial activity against one of the four microorganisms tested and two compounds (C8 and NOBA) had a lower IC50 in HeLa cells.